Photo-Stability of Dye Doped Sol Gel Glassy Matrices (Trinity Journal of Management, IT & Media (TJMITM), 2010)
The photo-stability of the dye  determines the longevity of solid-state  dye laser in which it is used. The  parameter is often determined by  measuring the photo-decay time of  dye with conventional fluorescence  spectrometer. In the present study the  Sol- Gel glasses matrix/ composites  were prepared using Sol-Gel  technique. Three dyes namely  Rhodamine 6 G (Rh-6G), Rhodamine  B (Rh-B) and Acrajlavine were doped  to prepare these lasing materials.  Fluorescence photo-bleaching was  measured in dye doped Sol-Gel  glasses/composites. The decay of  fluorescence signal versus cumulative  excitation energy was recorded.  These results are explained using a  simple model purposed by A. M.  Weiss et al.
Keywords: Dye laser; Sol-Gel; Fluorescence; Photo-stability